Synthesis of Spiro Heterocyclic Compounds - Mohamed N. Ibrahim; Mohamed F. El-Messmary; Mohamed G. A. Elarfi (E-Journal of Chemistry)
Reaction of isatin with acetophenone derivatives gave 3-hydroxy-3-phenacyl oxindole derivatives (II), dehydration of (II) gave 3-phenacylidene-2-indolinone derivatives (III). Condensation of (III) with hydrazine hydrate, phenylhydrazine and phenylthiourea afforded new spiropyrazolines (IV & V) and spiropyrimidinethione (VI) respectively. The structures of the final products were established by physical and spectral means.